Systematic Review of the Effect of Pneumococcal Conjugate Vaccine Dosing Schedules on Vaccine-type Invasive Pneumococcal Disease Among Young Children - Conklin, Laura (Williams & Wilkins, 2014)
BACKGROUND: Pneumococcal conjugate vaccines (PCV) are being implemented globally using a variety of different schedules. The optimal schedule to maximize protection of vaccinated children against vaccine-type invasive pneumococcal disease (VT-IPD) is not known. METHODS: To assess the relative benefit of various PCV dosing schedules, we conducted a systematic review of studies published in English from 1994 to 2010 (supplemented post hoc with studies from 2011) on PCV effectiveness against VT-IPD among children targeted to receive vaccine. Data on 2-dose and 3-dose primary series, both with and without a booster (“2+0,” “2+1,” “3+0” and “3+1”), were included. For observational studies using surveillance data or case counts, we calculated percentage reduction in VT-IPD before and after PCV introduction. RESULTS: Of 4 randomized controlled trials and 31 observational studies reporting VT-IPD among young children, none evaluated a 2+0 complete series, 7 (19%) evaluated 2+1, 4 (11%) 3+0 and 27 (75%) 3+1. Most (86%) studies were from North America or Europe. Only 1 study (observational) directly compared 2 schedules (3+0 vs. 3+1); results supported the use of a booster dose. In clinical trials, vaccine efficacy ranged from 65% to 71% with 3+0 and 83% to 94% with 3+1. Surveillance data and case counts demonstrate reductions in VT-IPD of up to 100% with 2+1 (6 studies) or 3+1 (17 studies) schedules and up to 90% with 3+0 (2 studies). Reductions were observed as early as 1 year after PCV introduction. CONCLUSIONS: These data support the use of 2+1, 3+0 and 3+1 schedules, although most data of PCV impact on VT-IPD among young children are from high-income countries using 3+1. Differences between schedules for impact on VT-IPD are difficult to discern based on available data.